1965
DOI: 10.1002/app.1965.070091001
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-induced crosslinking of poly(vinyl alcohol) in the presence of sensitizers

Abstract: SynopsisUltraviolet-induced crossliking of the film of polyvinyl alcohol with different degrees of polymerization was investigated in air a t 25°C. in the presence of sodium benzoate as a sensitizer.In the absence of the sensitizer, no crossliing occurred. The gel content increased with irradiation time, and tended to a limiting value, depending on the initial sensitizer concentration. The final gel content increased as a function of the initial amount of sodium benzoate. A plot of solubility ( S + AS'/^) agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The FTIR spectra of original PVA and PVA irradiated for 4 h are shown in Fig 1; they show that the absorption intensities at 1596 cm −1 (assigned to the CC stretching vibrations of the benzoate ring) and 1552 cm −1 (corresponding to the asymmetric carboxylate anion stretching) of sodium benzoate decreased after exposure to irradiation, indicating that the sensitizer was photo‐decomposed. These results are in agreement with previous studies8 using UV spectrophotometry to measure effects of irradiation on PVA in the presence of sodium benzoate. Takakura et al 8 detected spectral changes suggesting that, on irradiation, the sensitizer is initially converted to an intermediate (with an absorption maximum at a somewhat higher wavelength), which is further decomposed to a radical sufficiently reactive to abstract a hydrogen atom from the polymer.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The FTIR spectra of original PVA and PVA irradiated for 4 h are shown in Fig 1; they show that the absorption intensities at 1596 cm −1 (assigned to the CC stretching vibrations of the benzoate ring) and 1552 cm −1 (corresponding to the asymmetric carboxylate anion stretching) of sodium benzoate decreased after exposure to irradiation, indicating that the sensitizer was photo‐decomposed. These results are in agreement with previous studies8 using UV spectrophotometry to measure effects of irradiation on PVA in the presence of sodium benzoate. Takakura et al 8 detected spectral changes suggesting that, on irradiation, the sensitizer is initially converted to an intermediate (with an absorption maximum at a somewhat higher wavelength), which is further decomposed to a radical sufficiently reactive to abstract a hydrogen atom from the polymer.…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with previous studies8 using UV spectrophotometry to measure effects of irradiation on PVA in the presence of sodium benzoate. Takakura et al 8 detected spectral changes suggesting that, on irradiation, the sensitizer is initially converted to an intermediate (with an absorption maximum at a somewhat higher wavelength), which is further decomposed to a radical sufficiently reactive to abstract a hydrogen atom from the polymer. The FTIR spectra also show that the absorption intensities at 1388 cm −1 decreased after exposure to the irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PVA contains a number of hydroxyl groups, and it was demonstrated that PVA can be photocrosslinked under UV irradiation when using sodium benzoate as sensitizer (Follain et al, 2005;Takakura, Takayama, & Ukida, 1965). Therefore, it is worthy to apply the surface photocrosslinking modification method (Zhou et al, 2008) in TPS/PVA blend system to improve physical properties of the blend.…”
Section: Introductionmentioning
confidence: 99%
“…These processes can lead to the cross-linking of PVOH molecules, making the polymer more insoluble in water. The most efficient photosensitizer is sodium benzoate (SB), known to be photolysed by UV radiation [21,22]. Excitation of photoinitiator produces reactive radicals which initiate subsequent reactions in the polymer blend thus facilitating cross-linking between the two polymer chains [16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%